2022
DOI: 10.3390/antiox11071354
|View full text |Cite
|
Sign up to set email alerts
|

Clove Polyphenolic Compounds Improve the Microbiological Status, Lipid Stability, and Sensory Attributes of Beef Burgers during Cold Storage

Abstract: This study investigated the phenolic composition of clove powder extract (CPE), determined by high-pressure liquid chromatography, as well as the effect of the clove powder (CP) concentration (0, 2, 4, and 6%) on the quality of beef burgers during 21 days of cold storage at 4 °C. The CPE contained a high amount of total phenolic content (455.8 mg Gallic acid equivalent/g) and total flavonoid content (100.4 mg catechin equivalent/g), and it exhibited high DPPH antioxidant scavenging activity (83.9%). Gallic aci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 54 publications
0
7
1
Order By: Relevance
“…This convincingly manifested the high efficiency of the eugenol in the cryoprotection of the chilled pork. As previously mentioned, the eugenol had certain antimicrobial capacity and could reduce the decomposition of protein by microorganisms, which might also be the main reason for the less drip loss (Ahmed et al ., 2022).…”
Section: Resultsmentioning
confidence: 99%
“…This convincingly manifested the high efficiency of the eugenol in the cryoprotection of the chilled pork. As previously mentioned, the eugenol had certain antimicrobial capacity and could reduce the decomposition of protein by microorganisms, which might also be the main reason for the less drip loss (Ahmed et al ., 2022).…”
Section: Resultsmentioning
confidence: 99%
“…Similar observations were also reported by Augustyńska-Prejsnar et al (2021) and Hleap-Zapata et al (2020), who demonstrated the increased lightness of the cooked duck burgers incorporated with turmeric extract and paste, and chorizo incorporated with turmeric powder, respectively. However, it has been reported the reduction in lightness of the raw beef burgers after being treated with 2% of clove powder (Ahmed et al, 2022), while no effects of raw and cooked beef patties after being treated with 0.1% of clove extract (Zahid et al, 2019;Zahid et al, 2020;). Thus, this data variation suggested that the lightness could be affected by the interaction between the concentration, the presence of the pigment of the clove and heat intervention (cooking process) that would cause myoglobin denaturation, and modification of free water in the meat matrix (Sen et al, 2014;Sayas-Barberá et al, 2020;Ahmed et al, 2022).…”
Section: Colour Propertiesmentioning
confidence: 99%
“…However, it has been reported the reduction in lightness of the raw beef burgers after being treated with 2% of clove powder (Ahmed et al, 2022), while no effects of raw and cooked beef patties after being treated with 0.1% of clove extract (Zahid et al, 2019;Zahid et al, 2020;). Thus, this data variation suggested that the lightness could be affected by the interaction between the concentration, the presence of the pigment of the clove and heat intervention (cooking process) that would cause myoglobin denaturation, and modification of free water in the meat matrix (Sen et al, 2014;Sayas-Barberá et al, 2020;Ahmed et al, 2022). In addition, Fernández-López et al (2005), suggested that the colour of the products will be lightened, as the number of antioxidants increased, and would delay the metmyoglobin formation, which is responsible for the darker colour of meat products.…”
Section: Colour Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Oxidative reactions occur during the conversion of muscle into meat, meat processing, and storage, and constitute one of the main causes associated with the degradation of meat quality [4,69]. The oxidative process induces the degradation of lipid, protein, and color pigment, which leads to losses of nutritional value, texture changes, development of an off flavor and off odor, perceptions of rancidity, discoloration, and the development of toxic compounds, resulting in reduced shelf life [4,[69][70][71][72][73].…”
Section: Use Of Essential Oils In Meat Preservationmentioning
confidence: 99%